Daun Mangga (Mangifera indica L): Potensi Baru Penyembuh Luka Sayat - Arista Mutiara Risa; Yuni Pantiwati; Nurul Mahmudati; Husamah Husamah; Fuad Jaya Miharja (Biota, 2018)
The use of antiseptics in wounds can cause long-term side effects. This study aims to determine the potential of mango leaves (Mangifera indica L) as a natural ingredient for healing wounds. This true experimental research used six treatment groups. This study used a completely randomized design of four repetitions using 24 samples of white rats (Rattus norvegicus) taken randomly. The results of the Anova statistical test showed that there was a difference in the effect of giving mango leaf extract to incisive wound healing. The results showed that a concentration of 20% showed a faster recovery time of 7.25 days with an average wound closure of 4.02 mm. This indicates that the extract of mango leaves has the potential to be used as a healing wound for the incision.